Analysis of the biological implications of the mechanical environment within the growth plate during bone development in physiological and pathological scenarios - Guevara Morales, Johana María (2016)
The growth plate is a cartilaginous tissue located in the metaphysis of long bones that is responsible for their longitudinal growth. Such process is regulated in part by mechanical factors. In order to establish possible associations between specific mechanical stresses and biological responses in normal and pathological conditions, here it is presented a combined computational and experimental approach to this issues. Thus, initially we analyzed the mechanical environment within the growth plate at different developmental stages under physiological conditions, using finite element analysis. Then a mechanobiological model of cellular behavior within the growth plate was formulated, integrating biochemical, structural and mechanical factors. Finally, growth plate pathology was studied histologically in a genetic chondrodysplasia (MPS VI). and the potential effects of the observed abnormalities were explored using in silico modeling. Our results suggest that mechanical stimulation may play different roles during bone development. In addition, for the first time, it was described histologically the progression of the growth plate involvement in the rat model of MPSVI mainly characterized by loss of columnar arrangement. Moreover, it was evidenced that structural abnormalities observed in MPS VI growth plates rather than mechanical alterations may be an important factor contribution to skeletal pathology in this disease. This project is the first step towards the development of newr methodological approaches involving combined experimental and computational approaches to study growth plate behavior in physiological and pathological scenarios. Furthermore, results derived from this work will help elucidate mechanical events taking place within the growth plate and epiphysis during long bone growth. Additionally, the information generated may be useful to formulate h>potheses regarding mechanical influences on biological events taking place in normal and MPS bone growth.